Computer Solutions to Minimum-Cover Problems - Roth, R. (Operations Research, 1969)
A covering problem may be stated as follows: [Formula: see text] An algorithm has been programmed on the IBM 7094 for solving such problems. For a given problem, it generates a set of independent “locally-optimum” solutions. If p is the probability that any one solution is actually an optimum, then for n independently generated solutions we have a prob-babiiity of 1−(1 − p)n that an optimal solution appears in the set generated. Computational experience indicates that this approach yields good results for large problems (up to m · n ≦ 0.5 × 106).